Output-only modal identification of lively footbridges - F. Magalhães (2006)
This paper summarizes the dynamic tests recently performed in five German outstanding lively footbridges designed by Schlaich Bergermann & Partner, in the context of the European Project SYNPEX, and describes how the corresponding modal parameters (natural frequencies, mode shapes and modal damping ratios) were accurately identified on the basis of the application of modern and powerful stochastic modal identification techniques. (c) 2006 Taylor & Francis Group.